2007
DOI: 10.1068/p5587
|View full text |Cite
|
Sign up to set email alerts
|

Isovist Analysis Captures Properties of Space Relevant for Locomotion and Experience

Abstract: In a series of exploratory experiments we investigated interrelations between structure and shape of architectural indoor spaces on the one hand, and affective experience and navigation behaviour on the other hand. For this, isovist-based descriptions of 16 virtual indoor scenes were correlated with behavioural data from the experimental tasks. For all tasks-two active navigation tasks and an introspective appraisal of experiential qualities--strong correlations between subjects' behaviour and a small set of q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 30 publications
2
47
2
Order By: Relevance
“…The depth profiles were used to compare spatial properties of the left and right path alternative (left and right half of the stimulus). Earlier research suggests that line of sight (Conroy Dalton, 2003) and the local spatial complexity (Wiener et al, 2007) influence navigation and wayfinding behavior. Accordingly, we calculated longest line of sight for both path alternatives as well as the number of straight line segments to approximate their the spatial complexity.…”
Section: Stimulimentioning
confidence: 99%
See 1 more Smart Citation
“…The depth profiles were used to compare spatial properties of the left and right path alternative (left and right half of the stimulus). Earlier research suggests that line of sight (Conroy Dalton, 2003) and the local spatial complexity (Wiener et al, 2007) influence navigation and wayfinding behavior. Accordingly, we calculated longest line of sight for both path alternatives as well as the number of straight line segments to approximate their the spatial complexity.…”
Section: Stimulimentioning
confidence: 99%
“…Areas in the stimuli in which the profile is high relate to areas in space that are distant and vice versa. This analysis was chosen, because (1) the spatial situation is described from the perspective of the beholder capturing behaviorally relevant properties of space (Wiener et al, 2007;Franz & Wiener, 2008); (2) the visual system is able to use functionally equivalent information (i.e. angular declination) for distance judgments (Ooi, Wu, & He, 2001); (3) recent approaches in computational vision demonstrate that this information can also be computed directly from the image, even for complex natural outdoor scenes (Hoiem, Efros, & Hebert, 2007).…”
Section: Stimulimentioning
confidence: 99%
“…Invariably, this invokes geometry approaches that rely on central lines of tendency in the arrangement of urban morphology [130,389]. This work is in some senses adapted from the viewshed analysis of terrain, where afforded views can be interpreted by "isovists" (lines of equal vista) [125,390].…”
Section: Visionmentioning
confidence: 99%
“…Although virtual agents navigate the environment purely guided by its visual properties and lack any intentionality, they could robustly reflect how people move in real-world scenarios. "The agent can infer the affordances of the environment, or at least information on the global spatial relations visible from their current position in the environment" (Penn and Turner 2001:105), Two German psychologists (Wiener and Franz 2005;Wiener, Franz et al 2007) have recently undertaken a set of virtual experiments using isovist analysis as a means to disclose subjective valuation of space. In the first of these experiments, Wiener and Franz (2005) constructed sixteen virtual rooms resembling art galleries.…”
Section: Figure 1: Example Of An Isovist At An Intersectionmentioning
confidence: 99%
“…In another experiment Wiener and Franz (2007) asked subjects to navigate in virtual rooms of different shapes (and hence, of different isovist characteristics) and then to describe these rooms according to a protocol. They found that qualitative valuation of scenes was highly related to certain isovist properties, specifically to what the authors called an isovist "complexity," which was based on an isovist's area and perimeter.…”
Section: Figure 1: Example Of An Isovist At An Intersectionmentioning
confidence: 99%